Pelatihan Budidaya Ikan Air Tawar dan Peluang Pemasaran: Freshwater Fish Cultivation Training and Marketing Opportunities - Firdaus, Rahmad; Hermanto, Hermanto; Nugroho, Fithriawan; Maryani, Cik; Fauzi, Aditya Ahmad; Suhardi, Suhardi; Marna, Marna (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The freshwater fish farming and digital marketing training program for communities in Central Bangka Regency aims to improve participants' technical skills and marketing abilities to support the regional economy. This program is implemented through activities including theoretical learning about aquaculture, direct practice, and digital marketing training. This Community Service activity uses survey and observation methods to measure the impact of training on participants' technical understanding, productivity, and income. The results of the community service activities showed a significant increase in technical knowledge, digital marketing skills, and aquaculture productivity. Participants' understanding of pond management, seed selection, feeding techniques, and disease control increased significantly. In addition, participants' average monthly income increased by 30% after training. This program effectively equips communities with relevant skills, demonstrating that integrated training that includes technical and digital marketing aspects can drive economic growth in rural communities.